Mechanism of Fluoroquinolone Resistance Is an Important Factor in Determining the Antimicrobial Effect of Gemifloxacin against Streptococcus pneumoniae in an In Vitro Pharmacokinetic Model - MacGowan, Alasdair P. (American Society for Microbiology, 2003)
Antibacterial effect and emergence of resistance to gemifloxacin and levofloxacin were studied in an in vitro pharmacokinetic model of infection. A panel of Streptococcus pneumoniae strains with known mechanisms of resistance were used; two strains had no known resistance mechanism, two had efflux pumps, three had gyrA plus parC mutations, and one had only a parC mutation. Gemifloxacin MICs were in the range of 0.016 to 0.25 mg/liter, and levofloxacin MICs ranged from 1 to 16 mg/liter. Antimicrobial effect was measured by area under the bacterial-kill curve up to 72 h, and emergence of resistance was determined by population analysis profile before and during drug exposure. The area under the curve (AUC)/MIC ratios for gemifloxacin and levofloxacin were 35 to 544 and 3 to 48, respectively. As expected on the basis of these AUC/MIC ratio differences, antibacterial effect was much greater for gemifloxacin than levofloxacin. In the gemifloxacin simulations, mechanism of resistance as well as MIC determined the antibacterial effect, as indicated by gemifloxacin’s greater effect against efflux strains compared to those with gyrA or parC mutations despite similar MICs. This was not true of levofloxacin. Emergence of resistance was not easily demonstrated with either agent, and mechanism of resistance did not have any impact on it.